Polygenic risk for psychiatric disorders correlates with executive function in typical development. (10th May 2018) - Schork, A.J.; Brown, T.T.; Hagler, D.J.; Thompson, W.K.; Chen, C.‐H.; Dale, A.M.; Jernigan, T.L.; Akshoomoff, N.; ,
Abstract : Executive functions are a diverse and critical suite of cognitive abilities that are often disrupted in individuals with psychiatric disorders. Despite their moderate to high heritability, little is known about the molecular genetic factors that contribute to variability in executive functions and how these factors may be related to those that predispose to psychiatric disorders. We examined the relationship between polygenic risk scores built from large genome‐wide association studies of psychiatric disorders and executive functioning in typically developing children. In our discovery sample ( N  = 417), consistent with previous reports on general cognitive abilities, polygenic risk for autism spectrum disorder was associated with better performance on the Dimensional Change Card Sort test from the NIH Cognition Toolbox, with the largest effect in the youngest children. Polygenic risk for major depressive disorder was associated with poorer performance on the Flanker test in the same sample. This second association replicated for performance on the Penn Conditional Exclusion Test in an independent cohort ( N  = 3681). Our results suggest that the molecular genetic factors contributing to variability in executive function during typical development are at least partially overlapping with those associated with psychiatric disorders, although larger studies and further replication are needed. Abstract : Aggregate polygenic risk for Major Depression and Autism are associated with executive function.